Evaluation quality of sugar beet grown on soils highly infected with rhizomania - Došenović Irena S. (Zbornik Matice Srpske za Prirodne Nauke, 2006)
A field trial study with sugar beet varieties having different resistances to Rhizomania was conducted at two test sites in 2004. The field trials were located at Ruma (the Agricultural station) and at Sremska Mitrovica (the Institute of Agriculture). At both locations, twenty-one sugar beet varieties and a control variety (intolerant to the disease) were planted. The selected varieties were provided from several seed companies distributing seed material in Serbia. At Ruma, the difference between the first-ranked variety Alvira (100.82 t/ha) and the control variety (61.63 t/ha) was 39.19 t/ha or 38.87%. But, significant variability in processing quality within varieties and the control variety was observed. For example, the difference between root sugar contents of the first-ranked variety and the control one amounted to 4.64% absolute. At Sremska Mitrovica, significant variability of the observed parameters within varieties was also found. The highest sugar yielding variety was Leila (15.66%) producing better results for 3.42% absolute in comparison to the control variety. This variety produced good stands for the other parameters, too.